Solid gas and electrochemical hydrogenation properties of the R1-xR’xMgNi4-yCoy (R, R’ = Y, La, Ce) alloys - Verbovytskyy, Yu. V.; Zavaliy, I. Yu.; Berezovets, V. V.; Lyutyy, P. Ya. (Physics and Chemistry of Solid State, 2020)
New R1-xR’xMgNi4-yCoy (R, R’ = Y, La, Ce; x = 0.5; y = 0, 1, 2) alloys have been synthesized by powder sintering method, and their crystal structure and hydrogen storage properties have been studied. X-ray diffraction analysis showed that R1-xR’xMgNi4-yCo alloys belong to the MgCu4Sn-type structure. The synthesized alloys absorb hydrogen at room temperature and hydrogen pressure 0.1-10 bar. For some of the studied compounds, the formation of hydrides with cubic and orthorhombic structures was found. Highest hydrogen content is found for the Co-rich compounds: La0.5Y0.5MgNi2Co2H5.18 and La0.5Ce0.5MgNi2Co2H6.48. Electrochemical studies showed that Y-based electrode materials exhibit better electrochemical performance comparing with Ce-doped ones. Highest discharge capacity of 292 mА∙h/g was observed for La0.5Y0.5MgNi3Co, but the best cyclic stability after 50th cycle of 92% was seen for La0.5Y0.5MgNi2Co2. Additionally, obtained results of the electrochemical properties were compared with related compounds. High rate dischargeability of Co-free alloys at I = 1 A/g were twice higher than ones containing cobalt.